Proton pump inhibitor use and risk of depression and anxiety in children: nationwide cohort study - Yun‐Han Wang; Viktor Wintzell; Jonas F. Ludvigsson; Henrik Svanström; Björn Pasternak (Wiley, 2022)
Abstract Although some data have linked proton pump inhibitor (PPI) use to risk of depression and anxiety, there are no studies investigating this safety issue in children. This study investigated the association between PPI use and risk of depression and anxiety in children. We conducted a nationwide register‐based cohort study in Sweden, July 1, 2007, to December 31, 2016. Following matching on age and propensity score, we included 29,320 pairs of PPI initiators and noninitiators among children aged 7-17 years old. The primary analysis examined the risk of incident depression and anxiety, a composite outcome defined as a diagnosis of depression, anxiety, or a prescription for an antidepressant. Children who initiated PPI use had higher hazards for risk of depression and anxiety compared with noninitiators (hazard ratios [HRs], 2.61; 95% confidence interval [CI], 2.32-2.94). In analyses of the timing of depression and anxiety onset after PPI initiation, the HRs were 3.71 (95% CI, 2.17-6.34) for 1-30 days, 3.47 (95% CI, 2.33-5.18) for 31-90 days, 2.71 (2.04-3.60) for 91-180 days, 2.52 (2.00-3.16) for 181-365 days, and 2.34 (1.94-2.82) for 366-730 days. Significant associations were observed across all age groups. The magnitude of the association increased with longer duration of PPI use (p for trend < 0.0001). The association was consistent through all sensitivity analyses, including high‐dimensional propensity score matching (HR, 2.31, 95% CI, 2.05-2.61). PPI use was associated with increased risk of depression and anxiety in children. Further investigation is warranted to confirm or refute this potential association.